Ideologia Incel - un posibil risc asupra criminalității cibernetice - Raluca Alexandra ALBESCU; Diana-Zoe PETRESCU (Revista Română de Informatică și Automatică, 2023)
On social media, the way identity is presented is a misrepresentation of reality, which does not set the proper framework and opens the way for Incel ideology and other equally severe societal problems. Essentially, there is a fine line between having a place to vent emotionally and developing your identity and encouraging beliefs and attitudes that society does not want. The first one is positive, while the second one risks causing harm to others, both physically and emotionally. The anonymity of the internet can promote an aggressive and sometimes borderline violent environment when opinions clash. In fact, the online environment is now a more effective and globalised way of spreading extremist messages and targeting disaffected and marginalised young people to enlist them in violent causes. In fact, the online environment is now a more effective and globalised way of spreading extremist messages and targeting disaffected and marginalised young people to enlist them in violent causes. This article aims to provide an informed understanding of the Incel ideology's scope and nature. The paper considers how the Incel ideology has evolved, including its changing perspective, to demonstrate how members of this community can be a factor in the rise of cybercrime.